RESILIENSI DALAM KELUARGA: PERSPEKTIF PSIKOLOGI - Marty Mawarpury; Mirza Mirza (State Islamic University (UIN) Ar-Raniry, 2017)
The family is the smallest institution in society. A generation is forming from a family. That is why, the building of a family must strong to produce a formidable generation. Family toughness is determined by the foundation of the family builder. Resilience is often defined as endurance. Resilience is generally defined as the ability to overcome adversity, or to thrive despite challenges and difficulties in life. The concept of resilience is becoming increasingly popular in research on the ways people, families and communities recover from trauma, such as trauma from disasters, wars, or the loss of family members. A study of family resilience becomes important because the family is where people grow and develop. In addition, the family is the site of the main activity of the person so that the family become a quality determination of a person facing the future. To understand the process of family resilience, a multi system review is necessary in view of family conditions. The ecological perspective put forward by Urie Bronfenbrenner builds a model of interrelated relationships between families and between families and the social context.